Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5812/mejrh.65080
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression Among Primary Caregivers of Stroke Survivors in Nigeria

Abstract: Background: Stroke has a great adverse effect not only on the lives of stroke survivors but also on the informal caregivers, as they provide care ranging from assistance in activities of daily living, leading to a high risk of depression and other psychological morbidities. Objectives: This study explored the prevalence of depression and associated factors among primary caregivers of stroke survivors in Nigeria. Methods: A cross sectional survey on the prevalence of depression among primary caregivers of strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
(24 reference statements)
2
1
1
3
Order By: Relevance
“…Nonetheless, in both groups, the rates of depression found in our study fell within the ranges reported in the literature. 10,15,24,26,27 A similar observation was noted in another study that recruited patients and caregivers, in which the burden of patient depression exceeded that of the depression burden in the caregiver cohort in terms of both prevalence and severity. 12 Different factors may contribute to this observation.…”
Section: Discussionsupporting
confidence: 74%
“…Nonetheless, in both groups, the rates of depression found in our study fell within the ranges reported in the literature. 10,15,24,26,27 A similar observation was noted in another study that recruited patients and caregivers, in which the burden of patient depression exceeded that of the depression burden in the caregiver cohort in terms of both prevalence and severity. 12 Different factors may contribute to this observation.…”
Section: Discussionsupporting
confidence: 74%
“…A ideação suicida está frequentemente atrelada à presença constante de vivências de sofrimento e alterações psicológicas, sobretudo, a depressão, tornando o indivíduo mais vulnerável ao sofrimento emocional à ocorrência de pensamentos de frustração e inutilidade (4,(14)(15) . A depressão é um problema bastante comum entre cuidadores de pessoas que requerem cuidados de longa duração, como os sobreviventes de acidente vascular encefálico, tornando-se fator que pode predispor o cuidador à violência autoinflingida e ao suicídio (7,16) .…”
Section: Discussionunclassified
“…Diante disso, muitos cuidadores vivenciam momentos de tensão, ansiedade, estresse e depressão, principalmente por terem que assumir novo papel para o qual não apresentam conhecimentos ou mesmo capacitação, o que pode desencadear fortes emoções, sentimentos de incapacidade e de revolta e ausência de perspectivas futuras, proporcionando maior vulnerabilidade ao adoecimento psíquico e ao suicídio (7,(18)(19) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In African study done in Nigeria Yobe State Specialist Hospital showed that 65.3% individual had depression [20]. Similarly the study done in Nigeria 46.1% patients was experienced depression among stroke survivor [21]. The study done in orthopedic trauma patient of Ethiopia, the depressive symptoms was ranged from 36.1 to 36.4% [22,23].…”
Section: Introductionmentioning
confidence: 87%